Motivations behind daily preventative household food waste behaviours: The role of gain, hedonic, normative, and competing goals - Nguyen, Trang Thi Thu; Malek, Lenka; Umberger, Wendy J.; O'Connor, Patrick J. (Sustainable production and consumption, 2023)
The relationships between consumers' motivations, food management behaviours, and food waste are complex and depend on multiple motivational and health-related competing goals. This study uses Goal-Framing Theory and Structural Equation Modelling using data from a household survey (n = 1030) to demonstrate that multiple motivations, including gain, hedonic, normative, and competing motivations, can influence food waste through the mediations of daily food management behaviours (i.e. planning, purchasing, storing, preparing, and managing leftovers). The normative goal emerges as the most significant driver of food waste reduction through four food management behaviours, except purchasing behaviour. The gain goal exerts the second-largest effect on food waste reduction and is associated with all five food management behaviours. The hedonic goal shows weaker associations with food waste reduction, primarily manifesting in phases involving the physical disposal of food (e.g. managing leftovers). Importantly, the competing goal related to health and food safety concerns emerge as the strongest motivation leading to increased food waste. Among the food management behaviours, over-purchasing and consuming leftovers have the largest effects on food waste, presenting two critical points for interventions, especially in the context of consumer-retailer engagement, where the normative motivation is absent while the gain and hedonic motivations for food waste reduction are weak. Understanding the underlying motivations associated with specific behaviours provides valuable guidance for identifying ways to motivate households to change behaviours in relevant domains, ultimately contributing to reductions in food waste and fostering more sustainable practices.